Pemanfaatan Sampah Plastik Dalam Pembuatan Ecobrick Pada Kegiatan Pengabdian Masyarakat di SDN 46 Cakra Negara, Kota Mataram - Ega Dwi Putri Rahayu; Ali Harris; Nuzuly Ilmia Cerminand (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Plastik waste in Indonesia has become a serious problem that everyone must pay attention to. Very high use of plastik can affect environmental problems, human health and the economy. The high use of plastik and lack of adequate waste management infrastructure has led to large accumulations of plastik waste in this country. Plastik waste that we throw away carelessly can pollute rivers, oceans, land and threaten biodiversity, and can even cause natural disasters such as floods. The aim of making Ecobricks is to be a solution in reducing the accumulation of plastik waste. Ecobricks can be used in making home furniture such as. Chairs, tables, walls, and can be used as environmentally friendly buildings. Community service method with SDN 46 Cakra Negara students in dealing with the problem of plastik waste with direct practice in making Ecobricks. Results: In community service, the author uses used household plastik waste and food packaging around the author's house. Conclusion: Community service involving class V girls at SDN 46 Cakra Negara has run smoothly according to the processes and methods used so that class V girls are very enthusiastic in carrying out activities regarding waste management by utilizing household waste. Ecobricks are one option in dealing with environmental problems caused by plastik waste.